Consumer-oriented new product development: a review of recent developments. (1st January 2013) - Voulgari, Sotiria; Tsafarakis, Stelios; Grigoroudis, Evangelos; Matsatsinis, Nikolaos
Firms need to continuously develop new products or redesign their existing ones, due to the intense competition they are facing, as well as the rapidly changing economical and sociopolitical environment. In this context, consumer behaviour modelling has become an important and inextricable part of successful new product development during the last decades. This paper constitutes a survey of the literature in consumer-oriented new product development. We review a total of 60 research propositions in consumer behaviour modelling as a part of the product development procedure. The findings indicate a trend for integrative methodologies that approach the new product development process from both a marketing and an engineering perspective. The incorporation of dynamic consumer behaviour models into the product development methodologies seems to be the most promising area for future research.